On the Experience of Being Replicated - Brooke, John Hedley (Zygon, 2024)
This article provides an informal account of the experience of being replicated, with a summary of the original author’s earliest misgivings. It then identifies features of the third chapter of the book Science and Religion that may make it peculiarly resistant to replication. Then, the questions are addressed whether and how a replication itself should be replicated. Finally, the article provides reflection on the value of replication by responding to the earlier contributions led by Hans Van Eyghen and Rachel S. A. Pear in this thematic section.